Evolution of the core clinical features of dementia with Lewy bodies: Neuropsychiatry and behavioral neurology: DLB and FTD ‒ clinical manifestations. (7th December 2020) - Choudhury, Parichita; Radford, Jonathan Graff; Wurtz, Lincoln; Aakre, Jeremiah A.; Brushaber, Danielle; Jones, David T.; Knopman, David S.; Kantarci, Kejal; Savica, Rodolfo; Graff‐Radford, Neill R.; Drubach, Daniel A.; Fields, Julie A.; et al.
Abstract: Background: Dementia with Lewy Bodies (DLB) is the second most common cause of degenerative dementia but the evolution of the core clinical features of DLB has not been clearly defined. The objective of this study was to identify the temporal relationship between each core feature from the estimated onset of cognitive symptoms. Method: Participants include 485 patients with probable DLB who were evaluated at the Mayo Clinic Alzheimer Disease Research Center with neurologic and neurocognitive assessment. Each core clinical feature was compared using Kaplan‐Meier (KM) curves with the sentinel event representing age at which each core feature developed, or time from estimated cognitive onset. Result: The sample was disproportionately male (76%). Patients were followed longitudinally, with 84% followed until death. Mean MMSE at the last evaluation was 18.3 ± 7.8. KM curves for age of onset and cumulative incidence for DLB core features as time from cognitive onset are provided. REM‐sleep behavior disorder (RBD) developed earliest and in 77% of our sample with a median KM survival estimate of 69 years (95% CI: 67.6–70.8). RBD was present in greater than 50% of patients at cognitive symptom onset. The median KM survival estimate for cognitive symptom onset was 70.2 years (95% CI: 69.3‐71.0). Parkinsonism developed in 89% with a median KM survival estimate of 73.7 years (95% CI: 72.7‐74.7). 76% had fluctuations with a similar median KM survival estimate of 74.6 years (95% CI: 73.7‐75.8). Visual hallucinations (VH) were present in 70% emerging at a median KM survival estimate of 80.2 years (95% CI: 79.5‐ 81.3). Cumulative incidence estimates for median time from cognitive onset to parkinsonism, fluctuations and VH were 2 years (95% CI: 2.0‐2.5), 2.3 years (95% CI: 2.0‐3.2) and 4.3 years (95% CI: 4.0‐4.8 years), respectively. Conclusion: In this DLB cohort, RBD was most likely to precede cognitive onset. The evolution of the other core features after cognitive onset was parkinsonism and fluctuations and then VH. While VH occur about 4 years after cognitive symptom onset, parkinsonism and fluctuations occur within the first 2 years.